The preparative method of synthesis of functionalized 4,5-diarylsubstituted isoxazoles - Moskvina, V.S.; Shablykina, O.V.; Ishchenko, V.V.; Khilya, V.P. (Reports of the National Academy of Sciences of Ukraine, 2018)
Preparative methods for the synthesis of 2-(5-arylisoxazol-4-yl)benzoic acids and 2-(5-(2-hydroxyaryl)-isoxazol- 4-yl)benzoic acids have been developed. It is shown that amides of 2 ′ -deoxybenzoinecarboxylic acids are uni ver- sal starting compounds for the preparation of structurally diverse 4,5-diarylsubstituted isoxazoles.